Modelling the kinetics of seedless guava(Psidium guajava L.) peroxidase inactivation due to heat and thermosonication treatments. - Ganjloo, A.; Abdul Rahman, Russly; Bakar, Jamilah; Osman, Azizah; Bimakr, Mandana (IACSIT Press, 2009)

(untitled)
Effect of heat and thermosonication on inactivation kinetics of peroxidase in seedless guava have been studied over a temperature range of 80-95°C. Application of thermosonication was studied at 25, 50 and 75% of radiation intensity at the same temperature range. Ultrasonic wave’s intensity had significant(P<0.05) effect on peroxidase inactivation rate except the 25% intensity radiation. In both treatments, the enzyme kinetics showed a first-order kinetics model with monophasic behaviour. The activation energy, the rate constants were estimated which proving that the enzyme became more heat labile. Therefore, thermosonication can affect a process with reduced processing time and increased efficiency.